Custard Apple - Hodge, W. (Stephens Ltd., Trinidad, 2009)
A picture of a bunch of Custard Apples (Annona reticulata) on a branch. The fruits are variable in shape, heart shaped, oblong or irregular. The size ranges from 7 centimetres (2.8 in) to 12 centimetres (4.7 in). When ripe, the fruit is brown or yellowish, with red highlights and a varying degree of reticulation, depending on variety. The flavour is sweet and pleasant.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Fruit--Trinidad and Tobago; Annona reticulata